The “Passion of Exile”: Rebecca West's The Return of the Soldier - Bonikowski, Wyatt (Shell Shock and the Modernist Imagination, 2013)
Rebecca West's novel The Return of the Soldier emphasizes the importance of the theme of ‘return’ in the literature of the First World War. Soldiers returned from the First World War estranged and alienated from a home that could not accept them. While West's novel makes only a single reference to ‘shell-shock’, the term's history as site of definitional conflict seems important to West's narrative of a search for knowledge. Civilians have a psychical investment, in a successfully fought war and in the health of the soldier, since these help to maintain a collective fantasy of heroism and omnipotence. Jenny's interest in a ‘spiritual’ meaning of shell shock beyond its connection to a specific ‘material’ event of war may be compared to psychoanalysts' and military psychiatrists' attempts to find a cause in the internal processes of the psyche. Rebecca West's novel The Return of the Soldier emphasizes the importance of the theme of 'return' in the literature of the First World War. Soldiers returned from the First World War estranged and alienated from a home that could not accept them. While West's novel makes only a single reference to 'shell-shock', the term's history as site of definitional conflict seems important to West's narrative of a search for knowledge. Civilians have a psychical investment, in a successfully fought war and in the health of the soldier, since these help to maintain a collective fantasy of heroism and omnipotence. Jenny's interest in a 'spiritual' meaning of shell shock beyond its connection to a specific 'material' event of war may be compared to psychoanalysts' and military psychiatrists' attempts to find a cause in the internal processes of the psyche.